Optimizing Whatsapp Groups As A Multilayer Information Bridge From PPIC To Production: Rotogravure Flexible Packaging Industry In Sidoarjo - I Gede Putu Suardana,; Melania, Melania; Asruni, Asruni (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The Rotogravure Flexible Packaging industry plays a strategic role in supporting the manufacturing supply chain by providing high-quality packaging with protective and promotional functions. However, the success of the production process is highly dependent on the effectiveness of internal communication, particularly in delivering instructions from Production Planning and Inventory Control (PPIC) to production units. Layered communication patterns through Production Admins often lead to delays, miscommunication, and loss of critical information that may hinder production targets. This study aims to analyze the role of WhatsApp Groups as a digital communication medium to accelerate information flow and improve operational coordination effectiveness. This research uses a descriptive qualitative approach with data collected through in-depth interviews and observations involving PPIC, Production Admins, and operational units (Printing, Dry Lamination, Extrusion Lamination, Slitting, and Bag Making).The results show that WhatsApp Groups improve speed and accuracy of communication, provide traceable documentation, reduce idle time, and minimize instruction errors. Additionally, WhatsApp Groups support digital transformation through a paperless working system. Thus, WhatsApp Groups serve as an efficient and responsive communication bridge in the Rotogravure Flexible Packaging industry.